Prohibition of Notary Promotion and Publication in terms of UUJN - Yusticia wicaksono; Yuhelson Yuhelson; Felicitas Sri Marniati (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The purpose is written to remind again that there is a prohibition on promotion and publication based on Law No. 30 of 2004. The method is carried out by the author based on normative juridical methods. The formulation of the research is how the review of UUJN concerns the Position of a Notary on the form of promotion and publication of identity as well as the authority of a notary. Primary data of law no. 30 of 2004 which has been amended to Law no. 2 of 201 4 . Random secondary data for examples of violation cases in the form of advertisements for notary services from various digital sources. Tertiary data comes from studies such as journals, final research studies, and books that have been published digitally. Data is processed by reduction stages, adjustment of primary, secondary, and tertiary data with author's interpretation, and deduction. The research findings are that there are 3 articles that the authors found, namely article 9 paragraph (1) letter d, article 12 letter c, and article 17 letter a. These three articles indicate that there is a prohibition against promotion and publication.